Mājhī jīvana yātrā : Śrī. Da. Di. Kulakarṇī yāñce ātmacaritra - Kulkarni, Dattatray Digambar, 1909- (Suśilābāi Da. Kulakarṇī : prāptisthāna, Dattadigambara Yātrā Kampanī, 1978)
Autobiography of a proprietor of a travel agency.